Hot Speech and Exploding Bombs: Autonomic Arousal During Emotion Classification of Prosodic Utterances and Affective Sounds - Jürgens, Rebecca; Fischer, Julia; Schacht, Annekathrin (Frontiers in Psychology, 2018)
Emotional expressions provide strong signals in social interactions and can function as emotion inducers in a perceiver. Although speech provides one of the most important channels for human communication, its physiological correlates, such as activations of the autonomous nervous system (ANS) while listening to spoken utterances, have received far less attention than in other domains of emotion processing. Our study aimed at filling this gap by investigating autonomic activation in response to spoken utterances that were embedded into larger semantic contexts. Emotional salience was manipulated by providing information on alleged speaker similarity. We compared these autonomic responses to activations triggered by affective sounds, such as exploding bombs, and applause. These sounds had been rated and validated as being either positive, negative, or neutral. As physiological markers of ANS activity, we recorded skin conductance responses (SCRs) and changes of pupil size while participants classified both prosodic and sound stimuli according to their hedonic valence. As expected, affective sounds elicited increased arousal in the receiver, as reflected in increased SCR and pupil size. In contrast, SCRs to angry and joyful prosodic expressions did not differ from responses to neutral ones. Pupil size, however, was modulated by affective prosodic utterances, with increased dilations for angry and joyful compared to neutral prosody, although the similarity manipulation had no effect. These results indicate that cues provided by emotional prosody in spoken semantically neutral utterances might be too subtle to trigger SCR, although variation in pupil size indicated the salience of stimulus variation. Our findings further demonstrate a functional dissociation between pupil dilation and skin conductance that presumably origins from their differential innervation.